(untitled) (Jurnal Agribisnis dan Agrowisata, 2025)
The Influence of Instagram Social Media Marketing on Brand Engagement and Its Impact on Purchase Intention of Kalani Blooms Florist Products. This research was conducted at Kalani Blooms Florist in Bali. The purpose of this study is to determine the effectiveness level of social media marketing, brand engagement, and purchase intention, as well as to examine how social media marketing and brand engagement influence the purchase intention of Kalani Blooms Florist products in Bali. The type of data used in this research is quantitative data. The sampling technique applied was purposive sampling, with a total of 100 respondents who are Instagram followers of Kalani Blooms Florist and reside in Bali. The research instrument used to collect data was a questionnaire. The data were analyzed using the Structural Equation Model (SEM) method with the Smart-PLS program. The results of this study indicate that there is a significant influence of social media marketing on brand engagement, a significant influence of brand engagement on purchase intention, and a significant influence of social media marketing on purchase intention through brand engagement. Kalani Blooms Florist is advised to continue developing creative and interactive content strategies on Instagram to encourage consumer behavioral engagement and focus on optimizing conversion strategies from purchase intention into actual buying actions.